PERAN KOMPETENSI MANAJERIAL KEPALA SMP NEGERI 1 BATIPUH DALAM MENINGKATKAN MUTU SEKOLAH - Ardi Saputra (IAIN Batusangkar, 2018)
This study was aimed at finding out the role of managerial competence of the Principal of State Junior High School 1 Batipuh in improving the school’s quality as mandated in Minister’s Rule of National Education No. 13/2007. This study was categorized as case study of qualitative research. The sources of the data were the principal, teachers, and school employees. The data collection technique used in this research were observation, interview, and documentary study. To ensure the validity of this research, author used data triangulation of source, methods and time. The technique of data analysis was interactive model as stated by Miles and Huberman. This study showed that the role of the Principal's managerial competencies at in improving the quality of the school has been working very well, so that it brings the significant impact on the changing of the quality of the school. As the top leader in this school, he is able to perform his functions and roles. As a manager, he is able to influence and manage the school in order to give changes to the school as guided by Peraturan Menteri Pendidikan Nasional no. 3 tahun 2007, about the standard of the Principal of school/Madrasah, in which one of the competencies that must be mastered is managerial competence. The role of managerial competence of the Head Master of the school in improving the School quality, namely in designing school plan by creating cooperative relationship with the stakeholders of the school, namely the school teachers, school staffs, school committees, parents and the community. Moreover, he leaded the school by giving encouragement or motivation to the people in that school. He created conducive culture and comfortable situation for students in learning process, developed the curriculum, and provided services to develop the learners. Those things were closely linked with the role of the Principal to manage the facilities and infrastructures of the school, school finance, and to utilize advancees in technology and to establish a relationship with the community, as well as to monitor and to evaluate the quality of the school.